Estudo molecular dos genes alfa actinina 3 e ECA I/D em atletas de esportes de combate, artes marciais e lutas de alto rendimento: ênfase em luta de percussão - Netto, Zair Candido de Oliveira (2014)
Genetic factors and the environment are relevant points regarding the physical capacity of the human being. The objective of this study was to evaluate the genotype of genes, ACTN3 and ACE I / D with fighters in high yield in the form of percussion. In this study were part of the sample set of 15 high-level athletes in combat sports and martial arts, 6 fighters from Karate, 4 fighters Taekwondo, 4 fighters Muay Thai and 1 boxing. All fighters being present, all males with average age of 25.06 years with national and international experience in their respective weight classes and methods. Genotyping of polymorphisms of ACTN3 and ACE I / D was performed by polymerase chain reaction (PCR) chain from the genomic DNA. The genotypic and allelic frequencies were compared with control populations and athletes by Qui-Quadrado and Fisher exact tests for all analyzes was adopted P=0.05. The results obtained for genotypic and allelic frequencies of ACTN3 (RR = 35.71%, 57.14% and RX = XX = 7.14%; R = X = 64.28% and 33.71%) and ACE I / D (DD = 30.76%, 50.84% and ID = II = 15.36%; D = I = 65.2% and 34.8%) did not differ significantly from the control population e power sports In conclusion the data of this study follow the expected population in relation to genotypic and allelic frequency distribution in the ACTN3 gene and ACE I / D fighters of percussion.